Study of junior weight lifters' special fitness with different methods of speed-power training in preparatory period of general preparatory stage - O. B. Piven; V. Y. Dzhym (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: studying of junior weight lifters' special fitness in preparatory period of general preparatory stage. Material: 30 junior weight lifters of 12 - 14 years' old age were involved in experiment (2 nd and 3 rd sport grades). Results: optimal indicators of training by shock method have been determined for sportsmen of experimental group. Scope of loads was: squats with barbell on shoulders - lifting 779 times (90 tons); 310 jumps in depth and jumps out. Power indicators in total of combined exercises have increased by 16.5 kg. In control group other methodic was used. In control group scope of loads was: lifting of barbell - 910 times (111 tons). Power indicators in total of combined exercises have increased by 7.2 kg. Conclusions: the following regiment of training is recommended: first 3 weeks - jumps. Dozing and load scopes shall be as follows: first two trainings - two attempts (10 times each) with height of 0.5 m; third training - 3 attempts (10 times each) with height of 0.5 m; forth training - 4 attempts (10 times each) with height of 0.7 m. Jumps in depth shall be used 3 times weekly.